PERANCANGAN TAS RANSEL UNTUK MENDUKUNG PROTOKOL KESEHATAN - Khodijah, Tiara; Herlambang, Yanuar; Pujiraharjo, Yoga (Telkom University, 2023)
Abstrak: Awareness of maintaining cleanliness and health protocols is something that must be owned by every individual. Because by maintaining health protocols are one way to prevent the occurrence of a disease that can be transmitted. One way to prevent transmission is to bring personal equipment independently. With that, we need a container that can accommodate luggage. Because some public places have implemented a health protocol system, they do not provide personal items that are worn in general. By designing based on user needs and considering the efficiency of motion and time. Researchers have distributed questionnaires to find out the problems of each individual in their personal bag. The problem that often arises is that luggage is often mixed up, making it difficult to take small items and compartments that do not meet the needs. So, this design will pay more attention to the function aspect. And this aspect of function is expected to reduce existing problems, by designing a backpack with compartment features for various types of luggage that will be adapted to the needs of users during daily activities. Kata Kunci: ransel, efektivitas, kompartemen